Pelaksanaan Layanan Bimbingan untuk Mengatasi Anak yang Malas Belajar - Astri Putri Adinda; Annisa Nur Faizah Gaos; Rina Siti Nur Fatimah (ISLAMIKA, 2020)
Teaching activities carried out by professional teachers are not only oriented towards the dimensions of the creative faculties, but are of the dimension and intention. Because in the perspective of educational psychology, teaching in principle means the process of teacher actions that make students learn. This behavior includes open behaviors such as reading skills (the realm of intention), closed nature such as thinking (the realm of copyright) and feeling (the realm of feeling) each teacher is responsible for determining the formulation of specific and general learning targets as goals of teaching and learning activities which must be achieved after the teaching-learning process activities are finished. The importance of learning, there are three forms of development that occur in every human being, namely motor development, that is development related to changes in physical abilities (motor skills), cognitive development, that is development related to intellectual abilities, social and moral development, namely the development process related to the process changes in the way each individual communicates or relates to others, both as individuals and as groups.